Grundtvigs mageløse opdagelse. Et bidrag til dens tilblivelseshistorie. - Baagø, Kaj (Grundtvig-Studier, 1957)
Grundtvig s “Matchless Discovery” (a contribution to the history of its origin). By Kai Baagø. Grundtvig’s “matchless discovery” in 1825 that the faith of the Church as expressed in the Apostolic Creed existed before the Bible, and that we find in it the unshakable foundation on which we can build when the question is “What is true Christianity?” — this discovery was not unconnected with some ideas concerning Church policy and theology which came strongly to the fore among some young theologians in the winter and spring of 1825. 1) During this winter a young clergyman, Jørgen Thisted, began to make a violent attack particulary against the rationalistic Professor C. F. Hornemann, and it was precisely the Creeds which he used as his weapon; Hornemann’s exegesis of the New Testament was not in accordance with the Apostolic Creed, “inter alia”. Thisted was powerfully supported by a couple of young and learned theologians who had just returned from Germany: J. A. L. Holm and A . G. Rudelbach, who had been influenced especially by the Professors Tholuck and Neander in Berlin. During the same winter Rudelbach lectured at the University on the Creeds, and in their new periodical, “Theologisk Maanedsskrift” (“Theological Monthly”), of which Grundtvig was co-editor, Holm attacked Hornemann with the same weapons as Thisted. Undoubtedly these happenings drew Grundtvig’s attention to the significance of the Creeds in the fight against the rationalists. 2) Grundtvig also learnt something in this circle with reference to the question concerning the relation between the Bible and the Church. Rudelbach brought home from Germany the Lutheran Scriptural principle, which he stressed strongly in his writings, namely, that the right interpreting of the Scriptures can only be done by believers, that is, in the Church. It was precisely this view which Grundtvig put forward in “Kirkens Gienmæle” (“The Church’s Reply”) in the autumn of 1825. The Bible is indeed written for the Church (“menighed”), which was a fact before the Bible. Therefore theology in its interpretation must keep within the bounds which the Church’s confession of faith marks out. 3) Until 1825 Grundtvig had used the word “Kirke” (“church”) of the clergy and “menighed” (“congregation”) of the laity. Together with his “discovery” a new conception of the Church appears: the Church (“Kirke” as “corpus Christi”, the Church (“menighed”) gathered round the sacraments of Baptism and Communion, the Church (“menighed”) as the living chain of professing Christians. Here, too, he may have learnt much from his coloborator in the “Theologisk Maanedsskrift”, Rudelbach, who in his sermons and articles during 1824 and 1825 strongly stressed the conception of the Church as the Church of Christ, militant in this world, triumphant in the next, the Church of Christ, which exists wherever He feeds those who believe on Him with His own flesh and blood. 4) But the decisively new feature in Grundtvig’s “discovery” appears in the use which he made of the Apostolic Creed in his fight against the rationalists. Like the Early Church in its contest with the Gnostics, so, too, Grundtvig used “the historical argument” : that in the rule of faith (which for Grundtvig is the same as the confession of faith — the Creed) the right expression of true Christianity is to be found. He himself wrote, in a review of Neander’s “Antignosticus” which appeared in the spring of 1825, that Marheinicke and Neander in Germany brought this truth forth before him. There is therefore reason to believe that a study of Marheinicke’s “System des Catholicismus” (1810) and Neander’s book on Tertullian (“Antignostikus” 1825) led him to his new outlook. In both these works we also find a view concerning the Apostolic Creed, especially in its relation to the Scriptures,which is entirely parallel to that of Grundtvig.